PENGARUH WORK ABILITY (KEMAMPUAN KERJA), BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DINAS LINGKUNGAN HIDUP PROVINSI DKI JAKARTA - Hana Umi Majid, (2022)
This research is a type of quantitative research that aims to find out the influence of work ability, workload and work discipline on the performance of employees of the Jakarta Provincial Environment Office. The sample used as many as 62 employees. Data analysis technique is a method of inference analysis and processing data through IBM SPSS 25 with a significant rate of 5% or 0.05. The test results obtained the result that the work ability variable partially affects and significant on the performance variable because it has a calculated t value greater than the table t value (8,233 < 2.002) and a significance value of 0.000 > 0.05. The workload variable partially and significantly on performance has a calculated t value greater than the table's t value (8,904 > 2,002) and a significance value of 0.000 < 0.05. Similarly, the Work Discipline Variable (10,376 > 2,002) with significance (0.000 < 0.05). Simultaneously, variables in work ability, workload and work discipline have an effect and significant effect on performance variables because they get the value f calculates > from the table f (47,662 > 2.76) and a significant value of 0.000 < 0.05. The coefficient of determination test was obtained by 0.711 or 71.1% which means that 71.1% of performance is influenced by work ability, workload and work discipline.